Fostering Oral Interactions Through VLEs (2020)
ABSTRACT: This action research study conducted at a private school in Medellin was aimed at analyzing how first graders’ oral interaction can be fostered in a Virtual Learning Environment (VLE). Data were collected through a research journal, a checklist to measure students’ interactions, a questionnaire addressed to students, and an interview with the cooperating teacher. Data analysis showedthat oral interaction canactuallybe fostered in virtual environments. Moreover, a good language performance and positive attitudes can be developed,taking intoconsideration the importance of the teacher’s role in this process. These results were possible with first graders; it would be interesting to explore how these interactions take place with students of other ages.